(untitled) (Baghdad Science Journal, 2016)
This work included synthesis of several new polymers of polyacryloyl chloride in two steps . The first step the included the reaction of N-( sub. or un sub. benzoyl and sub. or un sub. acetyl ) amidyl sub. 2,6- diamino -4-methyl-1,3,5-triazine (1-5) by condensation of many substituted acid chlorides with 2,6- diamino -4-methyl-1,3,5-triazine . While the second step included the reaction of polyacryloyl chloride with the produced compounds (1-5) in step (1) in the presence amount triethyl amine (Et3N) to obtain new polyimides (6-10). The prepared compounds were characterized by UV. , FT-IR, and some of them by 1H-NMR and 13C- NMR spectroscopy.